2014
DOI: 10.1124/jpet.114.218065
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Pain: A Target for the Development of Novel Therapeutics

Abstract: Although current therapeutics provide relief from acute pain, drugs used for treatment of chronic pain are typically less efficacious and limited by adverse side effects, including tolerance, addiction, and gastrointestinal upset. Thus, there is a significant need for novel therapies for the treatment of chronic pain. In concert with chronic pain, persistent stress facilitates pain perception and sensitizes pain pathways, leading to a feed-forward cycle promoting chronic pain disorders. Stress exacerbation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 133 publications
(124 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, as psychotic-like experiences are common among those with depression and anxiety, some authors have suggested that they may be a non-specific marker of a wider spectrum of mental disorders other than psychotic disorders (Varghese et al, 2011) or a reflection of psychological distress (Saha et al, 2011b). As psychological distress is a strong correlate of pain (Johnson and Greenwood-Van Meerveld, 2014), it may have been an unmeasured contributor to the association between psychotic symptoms and pain in the current study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, as psychotic-like experiences are common among those with depression and anxiety, some authors have suggested that they may be a non-specific marker of a wider spectrum of mental disorders other than psychotic disorders (Varghese et al, 2011) or a reflection of psychological distress (Saha et al, 2011b). As psychological distress is a strong correlate of pain (Johnson and Greenwood-Van Meerveld, 2014), it may have been an unmeasured contributor to the association between psychotic symptoms and pain in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that psychotic symptoms are associated with decrements in health status (Nuevo et al, 2012), and that hospitalization not related to psychiatric causes and consumption of non-psychiatric drugs, as well as potentially painful conditions such as arthritis, angina, diabetes, tooth and mouth problems, and injuries are more common among those with psychotic symptoms compared to those with no such conditions (regardless of a psychosis diagnosis) (Moreno et al, 2013;Saha et al, 2011a). In addition, studies have also indicated that subclinical psychosis may be a non-specific marker of psychological distress (Saha et al, 2011b), which in turn, is strongly associated with the occurrence of pain (Johnson and Greenwood-Van Meerveld, 2014). This may mean that psychotic symptoms not reaching the threshold for a disorder may be highly prevalent in the population, and could be affecting population health either as a result of the symptoms themselves or through associated comorbidities.…”
Section: Introductionmentioning
confidence: 97%
“…(80) Further, the descending inhibitory pain pathways from the periaqueductal gray and rostral ventromedial medulla are inhibited by chronic stress through its effect on the prefrontal cortex and amygdala. (76) The emerging evidence suggests significant effects of meditation on brain areas, particularly prefrontal cortex, insula, cingulate and amygdala that influence pain perception. (81,82) The result is a change in appraisal cognitive processes with resulting enhanced emotional and cognitive control of pain.…”
Section: Possible Mechanism Of Actionmentioning
confidence: 99%
“…The brain is intimately involved in all these aspects. (76) Within the brain, the pain pathways connect with amygdala and insula to mediate the emotional response to the pain. (76) Other brain areas, including the prefrontal cortex, cingulate and parietal cortex inform about the quality and intensity of the pain.…”
Section: Possible Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation